The effect of various doses of gamma ray irradiation on growth and chlorophyll changes of three adlay genotypes - Qosim, Warid Ali; Anas, Anas; Amien, Suseno; Rachmadi, Meddy; Ramdani, Sidik; Islami, Romi Zamhir (Universitas Padjadjaran, 2024)
Adlay has great potential to be developed into an alternative food source in Indonesia because it contains carbohydrates and high fat. The aim was to effect of various doses of gamma-ray irradiation on growth,chlorophyll changes, and determination of lethal dose (LD50) three adlay genotypes in M1 generation. This study was conducted by using the experimental quantitative method without design. The material used consists of three adlay genotypes, including genotypes #28, #37, and #38. The seeds were treated with 0 Gy (control), 100 Gy, 200 Gy, 300 Gy, 400 Gy, and 500 Gy doses of gamma-ray irradiation by the Research Center for Radiation Process Technology, the National Research and Innovation Agency using Gamma Cell 220. The research was conducted at the Faculty of Agriculture Experimental Station, Universitas Padjadjaran, from December 2017 to July 2018. The LD50 was calculated by the curve-fitting analysis program based on characters of survival percentage, height seedling, root length, and appearance of leaf chlorophyll change in the three adlay genotypes. The results showed that the treatment of gamma-ray irradiation gave a diverse response to characters of survival percentage, height seedling and rooting length of the three adlay genotypes. There were LD50 for each genotype, 346 Gy for genotype #28, 381 Gy for genotype #37, and 371 Gy for genotype #38. The optimum dose of gamma-ray irradiation for the three adlay genotypes was 300 Gy. The appearance of chlorophyll change leaf the three adlay genotypes caused by gamma ray irradiation treatments with doses of 100 - 500 Gy were able to produce variation in the spectrum and frequency of different chlorophyll change in the M1 generation, the irradiation treatment of 400 Gy dose was able to make the highest frequency of chlorophyll mutations with a total frequency of 46.28%. Meanwhile, the gamma-ray irradiation treatment of 300 Gy produced the broadest chlorophyll mutant spectrum with 6 types of chlorophyll change consisting of tigrina, striata, viridis, variegata, maculata and albina green.